2019
DOI: 10.1002/acr2.1010
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Tofacitinib in the Treatment of Rheumatoid Arthritis in Open‐Label, Long‐Term Extension Studies up to 9.5 Years

Abstract: ObjectiveTofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). This post hoc analysis evaluated tofacitinib persistence in patients with RA in long‐term extension (LTE) studies up to 9.5 years.MethodsData were pooled from two LTE studies: ORAL Sequel (NCT00413699) and Study A3921041 (NCT00661661). Patients received tofacitinib 5 or 10 mg twice daily (BID), as monotherapy or with background conventional synthetic disease‐modifying antirheumatic drugs. Kaplan‐Meier estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
3
19
0
6
Order By: Relevance
“…Studies have demonstrated that the JAK inhibitors are almost identical to other biological agents in adverse events. However, tofacitinib has been associated with increased susceptibility to herpes zoster infection (Cohen et al, 2017;Curtis, Xie, Yun, Bernatsky, & Winthrop, 2016;J. Pope et al, 2017;Yamaoka, 2016a).…”
Section: Janus-activated Kinase (Jak) Inhibitorsmentioning
confidence: 99%
“…Studies have demonstrated that the JAK inhibitors are almost identical to other biological agents in adverse events. However, tofacitinib has been associated with increased susceptibility to herpes zoster infection (Cohen et al, 2017;Curtis, Xie, Yun, Bernatsky, & Winthrop, 2016;J. Pope et al, 2017;Yamaoka, 2016a).…”
Section: Janus-activated Kinase (Jak) Inhibitorsmentioning
confidence: 99%
“…Using mutually exclusive IBD and RA infliximab treatment data to bridge differences across the unique inflammatory diseases, the authors conclude that, after adjustment, adherence was higher with infusions than oral medications [1]. These results are in contrast to findings from previous well-conducted studies [2,3]. Furthermore, the analysis by Moran et al does not take into account a number of important factors, and we suggest relies on questionable methodology.…”
mentioning
confidence: 61%
“…Finally, published data on the concept of persistence and adherence with tofacitinib have demonstrated 2-and 5-year estimated drug survival rates of 75.5% and 49.4%, respectively, in a clinical trial setting [2], while real-world data comparing tofacitinib with common biologics (adalimumab, etanercept, and abatacept) for the treatment of RA reported persistence, and adherence of tofacitinib was at least comparable to that of the biologics [3].…”
mentioning
confidence: 97%
“…In the Comment letter, the authors state ''the authors conclude that after adjustment, adherence was higher with infusions than oral medications [1]. These results are in contrast to findings from previous well-conducted studies [2,3].'' We disagree that the two studies cited by the Comment authors provide evidence that adherence is higher with oral medications than with infusions.…”
mentioning
confidence: 82%